Pengembangan Pembelajaran Guru Sekolah Menengah Atas (SMA) Melalui Pemanfaatan Multimedia yang Menarik dan Efektif Di SMA Entrepreneurship Bi’rul Ulum Serang - Rudianto Rudianto; Basuki Rakhim Setya Permana; Hamdan Hamdan; Ardiyansah Ardiyansah (P3M FIA UNKRIS, 2023)
To improve the quality of learning in the Bi'rul Ulum Entrepreneurship High School environment, the use of multimedia in education has been the main focus of this study. The study also aims to explore and evaluate how the use of multimedia affects the learning of subject teachers, as well as how effective the use of multimedia is in increasing student engagement and understanding of the material. Involving a large number of students and teachers from various levels of education, qualitative and quantitative research methods were applied. Data was collected through interviews, observations, questionnaires, and evaluations of student learning outcomes before and after the implementation of multimedia. The results of the study showed that teachers and students responded well to the use of multimedia in learning. Teachers reported that students were more engaged and easier to deliver material, and students showed that they were more interested and understood what they learned after using media. In addition, the evaluation of student learning outcomes showed that the use of media improved student academic achievement. These results suggest that teachers should receive more in-depth training, create materials that are more integrated with technology, and create school policies that support the use of multimedia in learning. The study enhances our understanding of the role of multimedia in teacher learning development and shows its great potential to be utilised to improve the quality of education in the future. Keywords: multimedia in education, teacher learning development, technology in learning, utilisation of multimedia in teaching, effectiveness of multimedia in education